Influence of the background, substrate and thickness in light behaviour and colour of zirconia-reinforced lithium silicate (ZLS) glass-ceramic - Viegas, Diogo Cabecinha; Canhão, Rita; Riquieri , Hilton; Saavedra, Guilherme; Palmela, Adriana; Hermínio, Joana; Roque, João Carlos (Brazilian Dental Science, 2021)
.